Penerapan dan Analisis Phylosophical Theory Patricia Banner “Novice To Expert” pada Asuhan Keperawatan Chf - Humairah, Faradila; Nursanti, Irna (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Congestive Heart Failure (CHF) is the inability of the heart to maintain adequate cardiac output to meet metabolic and oxygen needs in the tissues despite adequate venous return, with signs and symptoms of shortness of breath and fatigue caused by abnormalities in the function of the heart structure. Patricia Benner's theory explains that practitioner knowledge produces new ideas in scientific disciplines. By using appropriate operational and theoretical terms to define the concepts in the theory. The theory developed by Patricia Benner has 5 levels